1992
DOI: 10.1288/00005537-199201000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of risk factors in juvenile‐onset and adult‐onset recurrent respiratory papillomatosis

Abstract: The clinical triad of a firstborn delivered vaginally to a young (teenage) mother has been previously noted among juvenile onset recurrent respiratory papillomatosis (JO-RRP) patients. This study was based on a questionnaire survey of JO-RRP patients, adult onset recurrent respiratory papillomatosis (AO-RRP) patients, and juvenile and adult controls. The survey results revealed that the complete or partial triad was observed in 72% of JO-RRP patients, 36% of AO-RRP patients, 29% of juvenile controls, and 38% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
1
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(134 citation statements)
references
References 9 publications
3
122
1
8
Order By: Relevance
“…Also, conversion to laryngeal carcinoma occurs more frequently in juveniles [6,7]. In addition to having a different clinical course, JO-RRP differs in its route of acquisition; while numerous studies have indicated that vertical transmission from maternal genital condylomas is the primary mode of juvenile papillomas, adult papillomas apparently spread secondary to oral-genital contact [8,9]. The differences in incidence, transmission, and clinical course of JO-RRP versus AO-RRP suggest that the HPV phenotype may also vary between the two.…”
Section: Introductionmentioning
confidence: 99%
“…Also, conversion to laryngeal carcinoma occurs more frequently in juveniles [6,7]. In addition to having a different clinical course, JO-RRP differs in its route of acquisition; while numerous studies have indicated that vertical transmission from maternal genital condylomas is the primary mode of juvenile papillomas, adult papillomas apparently spread secondary to oral-genital contact [8,9]. The differences in incidence, transmission, and clinical course of JO-RRP versus AO-RRP suggest that the HPV phenotype may also vary between the two.…”
Section: Introductionmentioning
confidence: 99%
“…Benign tumors are caused by low risk types such as HPV 1, 2, 3, 4, 6, 10, 11 and others. 9) No simple culture method or serologic test is available for identifying HPV infection. Techniques for identifying the virus are based on nucleic acid detection, either direct hybridization or PCR amplification.…”
Section: Discussionmentioning
confidence: 99%
“…In juvenile onset RRP, HPV is thought to be acquired at the time of vaginal delivery. 3) In one case control study, 9) adult onset RRP patients had more sexual partners and oral sex than their controls. HPVs cause latent airway infection, in addition to the active infection, that induces papillomas, and activation of latent HPV DNA, which appears to persist for the life of the patient, is considered to be the cause of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with low-oncogenic risk HPVs (LR-HPV), such as HPV-6 and 11, can cause benign lesions of the anogenital areas known as Condylomata acuminate (genital warts), a large proportion of low-grade squamous intraepithelial lesions (LSIL) of the cervix, oral papillomas as well as conjunctival papillomas. HPV-6 or 11 may also cause in rare instance recurrent respiratory papillomatosis, which in infants and young children can be very morbid and usually perinatally transmitted (Armstrong et al 2000) whereas in adult it is usually sexually transmitted and less severe than in children (Kashima et al, 1992). 18,31,33,35,39,45,51,52,56,58,11,13,26,30,32,34,42,44,53,54,61,62,66,67,68,69,70,71,72,73,74,81,82,83,84,85,86,87,89,90 Cutaneous 1,2,4,5,8,9,12 ,1 4,15 ,17,19,20,21,…”
Section: Alpha-papillomavirusmentioning
confidence: 99%